المخاطر المشمولة بتغطية الضمان الاجتماعي - سارة لبيوض; الزهرة خمايسية (My University, 2017)
Summary: In the foregoing, we concluded that the social security system is an important and sensitive system concerned with all segments of society and that the Algerian social system has followed the example of other countries in social insurance. social security ", where all segments of society benefit from social security, which covers a range of social risks, In view of the circumstances in Algeria and the reasons that led to the change and revision of the social protection laws, the legislature has provided this reference with a series of laws. 1. The radical socio-economic transformation, where the country has moved from the planned to the market economy. Economy During 2 International competition and the gradual transformation of Algeria's economy in the global economy. Seeking to engage in WTO and enter into a partnership agreement with Europe still in the course of negotiation], and in order to enter into a future free exchange organization. . Thus, it is clear to us that the social security system is very important in terms of standards. .................................. الملخص : من خلال ما تقدم إختتمنا الى ان نظام الضمان الاجتماعي نظام هام و حساس يهتم بكافة الشرائح المجتمع و ان المنظومة الاجتماعية الجزائرية قد حذت حذو باقي الدول في التأمين الاجتماعي، حيث يستفيد جميع فئات المجتمع من الضمان الاجتماعي الذي يغطي مجموعة من المخاطر الاجتماعية ، فقد اطرا المشرع هذا المحال بمجموعة من القوانين إلا انها عرفت عدة تغيرات واسعة و ذلك نظرا للظروف التي تشهدها الجزائر و من الاسباب التي ادت الى تغيير و مراجعة قوانين الحماية الاجتماعية نذكر : 1. التحول الاجتماعي و الإقتصادي الجذري ، حيث عملت الدولة على الإنتقال من ا المخطط الى اقتصاد السوق. اقتصاد خلال 2 المنافسة الدولية و التحول التدريجي للاقتصاد الجزائري في الإقتصاد العالمي و ذلك من . سعيها في الانخراط في المنظمة العالمية للتجارة و الدخول في اتفاقية الشراكة مع اوروبا التي لا زالت في مسار التفاوض ] ، و لأجل الدخول في منظمة تبادل الحر مستقبلا. . وعليه تتضح لنا الأهمية البالغة لمسايرة نظام الضمان الإجتماعي و ذلك من حيث المعايير .................................... Résumé : Dans ce qui précède, nous avons conclu que le système de sécurité sociale est un système important et sensible concernant tous les segments de la société et que le système social algérien a suivi l’exemple d’autres pays en matière d’assurance sociale. sécurité sociale ", où tous les segments de la société bénéficient d’une sécurité sociale qui couvre un éventail de risques sociaux, Compte tenu des circonstances en Algérie et des raisons qui ont conduit à la modification et la révision des lois de protection sociale, le législateur a fourni cette référence par une série de lois. 1. La transformation socio-économique radicale, où le pays est passé de l’économie planifiée à l’économie de marché. Économie Pendant 2 La concurrence internationale et la transformation progressive de l’économie algérienne dans l’économie mondiale. Chercher à s’engager au sein de l’OMC et à conclure un accord de partenariat avec l’Europe toujours en cours de négociation], et afin d’entrer dans une future organisation de libre échange. . Il est donc clair pour nous que le système de sécurité sociale est très important en termes de normes.